Implementación de un proceso integrado para el tratamiento de aguas residuales industriales en planta Chao - Camposol S.A. - Perez Fernandez, Jhon Luis (2019)
ABSTRACT The present research work had the purpose of determining the impact of the implementation of an integrated process in the treatment of industrial wastewater in the agroindustrial plant CAMPOSOL S.A. in the period 2016 - 2017. To make the proposal of the treatment system, the amount of water eliminated from industrial processes was evaluated, then the status of the lagoons and their storage capacity was evaluated, determining capacity and days of storage of wastewater. After knowing the storage capacity, primary physical systems were implemented to reduce by 95% the organic solids in suspension generated from the processes, allowing to ensure an adequate treatment of wastewater with the retention of organic matter ensured by the preliminary systems, aquatic plants were introduced in the following lagoons as a pate of the biological increase, stabilizing ph parameters, total suspended solids, odors, color, among others. The final water of the clarifier is directed to a final reservoir in which chlorine is applied for its total disinfection and subsequent pumping for the irrigation of forests. It is concluded that the implementation of an integrated process significantly reduces industrial waste from the wastewater of the agroindustrial plant CAMPOSL S.A. in the period 2016 - 2017, a very beneficial result for the plant.